Pengaruh Temperature Tempering Terhadap Kekerasan Pada Baja Karbon Sedang Hasil Pengelasan FCAW (Flux-Cored Arc Welding) - Clara Sekeroney; Nevada. J.M Nanulaita; Frederick Dematacco; Mohammad Anas Fikri; Ike Dayi Febriana (Journal Mechanical Engineering, 2023)
Carbon steel is a type of alloy steel consisting of various elements, especially iron (Fe) and carbon (C). In general, the properties of steel are affected by the percentage of carbon and the microstructure of steel which is affected by steel composition and heat treatment. The welding process can change the structure and composition of steel. The safety of weld results can be carried out after welding using a heat treatment process. This tempering aims to obtain better and desired mechanical properties. Tempering is carried out using temperatures of 200⁰C, 250⁰C and 300⁰C with cooling using air media and mechanical testing will be carried out.The results of this research showed that tempering temperature had an effect on the hardness value of medium carbon steel resulting from FCAW welding. The hardness value at a temperature of 200℃ was 54.75, a temperature of 250℃ was 53.00 and a temperature of 300℃ was 52.04. The higher the temperature, the lower the hardness value and conversely, the lower the tempering temperature, the higher the hardness value.Keywords: Welding, Tempering, Hardness